2021
DOI: 10.3389/fphar.2021.714694
|View full text |Cite
|
Sign up to set email alerts
|

Houttuynia cordata Thunb: An Ethnopharmacological Review

Abstract: Houttuynia cordata Thunb (H. cordata; Saururaceae) is widely distributed in Asian regions. It plays an important role in traditional health care and disease treatment, as its aboveground stems and leaves have a long medicinal history in China and are used in the treatment of pneumonia and lung abscess. In clinical treatment, it can usually be combined with other drugs to treat dysentery, cold, fever, and mumps; additionally, H. cordata is an edible plant. This review summarizes detailed information on the phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 120 publications
(137 reference statements)
0
43
0
Order By: Relevance
“…Results suggested the palatability factor was a common consideration for locals when choosing plants to use as an accompaniment for grilled fish. Allium hookeri , Allium macrostemon and Houttuynia cordata showed 100% FL value, according to available studies [ 37 42 ]. These findings fully corroborated the availability hypothesis of such composite plants selected by the Dong people.…”
Section: Discussionmentioning
confidence: 97%
“…Results suggested the palatability factor was a common consideration for locals when choosing plants to use as an accompaniment for grilled fish. Allium hookeri , Allium macrostemon and Houttuynia cordata showed 100% FL value, according to available studies [ 37 42 ]. These findings fully corroborated the availability hypothesis of such composite plants selected by the Dong people.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have provided evidence that H. cordata possesses anti-inflammatory, anticancer, antioxidant and antiviral activities [65] , [66] , [67] . H. cordata has shown antiviral activities against the herpes and influenza viruses [68] . Lau et al [38] studied the aqueous extract of H. cordata using a fluorogenic protein-based assay and found that it exhibited potent activity against SARS-CoV-2 3CL pro at a concentration of 200 µg/mL.…”
Section: Medicinal Plants and 3cl Pro Activitymentioning
confidence: 99%
“…Throughout history, medicinal plants have always been valued sources of bioactive compounds that are used to prevent, treat and cure a host of common illnesses. The vast traditional knowledge of medicinal plants has accounted for 70-95% of treatment prescribed for many diseases especially in Asia, including India (X Wu et al, 2021). Important pharmacologically active compounds such as morphine (an analgesic), artemisinin and chloroquine (anti-malarial drugs), vinca alkaloids (cancer treatment), etc widely used in modern medicine are all plant-derived (Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%